Comparative transcriptomic profiling of peach and nectarine cultivars reveals cultivar-specific responses to chilled postharvest storage - Muto, Antonella; Bruno, Leonardo; Madeo, Maria Letizia; Ludlow, Richard; Ferrari, Michele; Stimpson, Louise; LoGiudice, Claudio; Picardi, Ernesto; Ferrante, Antonio; Pasti, Luisa; Müller, Carsten T.; Chiappetta, Adriana Ada Ceverista; et al. (Frontiers in Plant Science, 2022)
Introduction Peach (Prunus persica (L.) Batsch,) and nectarine fruits (Prunus persica (L.) Batsch, var nectarine), are characterized by a rapid deterioration at room temperature. Therefore, cold storage is widely used to delay fruit post-harvest ripening and extend fruit commercial life. Physiological disorders, collectively known as chilling injury, can develop typically after 3 weeks of low-temperature storage and affect fruit quality. Methods A comparative transcriptomic analysis was performed to identify regulatory pathways that develop before chilling injury symptoms are detectable using next generation sequencing on the fruits of two contrasting cultivars, one peach (Sagittaria) and one nectarine, (Big Top), over 14 days of postharvest cold storage. Results There was a progressive increase in the number of differentially expressed genes between time points (DEGs) in both cultivars. More (1264) time point DEGs were identified in ‘Big Top’ compared to ‘Sagittaria’ (746 DEGs). Both cultivars showed a downregulation of pathways related to photosynthesis, and an upregulation of pathways related to amino sugars, nucleotide sugar metabolism and plant hormone signal transduction with ethylene pathways being most affected. Expression patterns of ethylene related genes (including biosynthesis, signaling and ERF transcription factors) correlated with genes involved in cell wall modification, membrane composition, pathogen and stress response, which are all involved later during storage in development of chilling injury. Discussion Overall, the results show that common pathways are activated in the fruit of ‘Big Top’ nectarine and ‘Sagittaria’ peach in response to cold storage but include also differences that are cultivar-specific responses.